Spatial inequalities in Malaysia’s non-revenue water rates issues, challenges and management strategies - Lai, Chee Hui; Chan, Ngai Weng (2015)

(untitled)
In Malaysia, high non-revenue water (NRW) rate is amongst the country’s top water issues. NRW rates of all states in the country vary greatly, with the rates ranging from 18.2 to 62.4 per cent. This huge spatial variation is due to variations in management efficiency of the water operator, amount of funding for NRW reduction programme and level of public awareness. This paper aims to examine the effect of the spatial inequality on NRW management in Malaysia’s states by comparing NRW rates between states with different area sizes. The study is mainly based on literature review and secondary data. The results show that states with smaller surface areas recorded lower NRW rates but the smallest state was found to record the highest NRW rate. Factors such as service’s coverage area, population density, water supply network density, dispersal of the city area, and location of the water users, and type of water users also have significant impacts on NRW management. For example, high water supply network density, poor water resources availability and high demand in Penang have forced the state’s water operator to increase its efficiency in NRW management. In contrast, low water demand, low population density, and less commercial area in Perlis are found to be the reasons of high NRW rate in the state. In conclusion, spatial factors can impact NRW as smaller states can better manage NRW due to the smaller water service areas covered. However, states cannot use size of service area and spatial variations as excuses for high NRW as the study found that adequate funding, proper planning, effective management, efficient service, and proactive strategies of water operator are more important factors that can have significant impacts on the NRW rates.